Chromosome aberration and micronucleus frequencies in Allium cepa cells exposed to petroleum polluted water - A case study - Leme, Daniela Morais [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Elsevier B.V., 2008)
In the present study, we applied Chromosome Aberration (CA) and Micronucleus (MN) tests to Allium cepa root cells, in order to evaluate the water quality of Guaeca river. This river, located in the city of Sao Sebastiao, SP, Brazil, had been affected by an oil pipeline leak. Chemical analyses of Total Petroleum Hydrocarbons (TPHs) and Polycyclic Aromatic Hydrocarbons (PAHs) were also carried out in water samples, collected in July 2005 (dry season) and February 2006 (rainy season) in 4 different river sites. The largest CA and MN incidence in the meristematic cells of A. cepa was observed after exposure to water sample collected during the dry season, at the spring of the river, where the oil leak has arisen. The F, cells from roots exposed to such sample (non-merismatic region) were also analyzed for the incidence of MN, showing a larger frequency of irregularities, indicating a possible development of CA into MN. Lastly, our study reveals a direct correlation between water chemical analyses (contamination by TPHs and PAHs) and both genotoxic and mutagenic effects observed in exposed A. cepa cells. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Allium test; genotoxic effects; mutagenic effects; water quality; petroleum hydrocarbons